K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 8 2021

b. \(x^3+4x=0\)

\(\Leftrightarrow x\left(x^2+4\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x^2+4=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=0\\x^2=-4\end{matrix}\right.\) \(\Leftrightarrow x=0\) ( vì \(x^2\ge0\forall x\) )

Vậy \(x=0\)

19 tháng 8 2021

\(x^3+4x=0\)

\(\Leftrightarrow x\left(x^2+4\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=0\\x^2=-4\left(VL\right)\end{matrix}\right.\)

\(\Leftrightarrow x=0\)

Vậy x=0

4 tháng 8 2018

\(4x^2+4x-3=0\)

\(\left[\left(2x\right)^2+2.2x.1+1\right]-4=0\)

\(\left(2x+1\right)^2-2^2=0\)

\(\left(2x+1-2\right).\left(2x+1+2\right)=0\) 

\(\left(2x-1\right).\left(2x+3\right)=0\)

\(\Rightarrow\orbr{\begin{cases}2x-1=0\\2x+3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=-\frac{3}{2}\end{cases}}}\)

Vậy \(\orbr{\begin{cases}x=\frac{1}{2}\\x=-\frac{3}{2}\end{cases}}\)

\(x^4-3x^3-x+3=0\)

\(x^3.\left(x-3\right)-\left(x-3\right)=0\)

\(\left(x-3\right).\left(x^3-1\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x-3=0\\x^3-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}}\)

Vậy \(\orbr{\begin{cases}x=3\\x=1\end{cases}}\)

\(x^2.\left(x-1\right)-4x^2+8x-4=0\)

\(x^2.\left(x-1\right)-\left[\left(2x\right)^2-2.2x.2+2^2\right]=0\)

\(x^2.\left(x-1\right)-\left(2x-2\right)^2=0\)

\(x^2.\left(x-1\right)-4.\left(x-1\right)^2=0\)

\(\left(x-1\right).\left[x^2-4.\left(x-1\right)\right]=0\)

\(\left(x-1\right).\left[x^2-2.x.2+2^2\right]=0\)

\(\left(x-1\right).\left(x-2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}}\)

Vậy \(\begin{cases}x=1\\x=2\end{cases}\)

Tham khảo nhé~

30 tháng 12 2016

b)   ( 2x - 3 ) - ( 3 - 2x )( x - 1 ) = 0

<=> ( 2x - 3 ) + ( 2x - 3 )( x - 1 ) = 0

<=> ( 2x - 3 )( 1 + x - 1 ) = 0

<=> x( 2x - 3 ) = 0

\(\Leftrightarrow\orbr{\begin{cases}x=0\\2x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{3}{2}\end{cases}}}\)

Vậy .....

30 tháng 12 2016

a, 25x^2 - 1 - (5x -1)(x+2)=0

=> (5x)^2 - 1 + (5x-1)(x+2) = 0

=> (5x-1)(5x+1) + (5x-1)(x+2) = 0

=> (5x-1)(5x+1+x+2) = 0

=> (5x-1)(6x+3) = 0

=> \(\orbr{\begin{cases}5x-1=0\\6x+3=0\end{cases}}\)

29 tháng 11 2023

a: \(x^3-4x^2-x+4=0\)

=>\(\left(x^3-4x^2\right)-\left(x-4\right)=0\)

=>\(x^2\left(x-4\right)-\left(x-4\right)=0\)

=>\(\left(x-4\right)\left(x^2-1\right)=0\)

=>\(\left[{}\begin{matrix}x-4=0\\x^2-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x^2=1\end{matrix}\right.\Leftrightarrow x\in\left\{2;1;-1\right\}\)

b: Sửa đề: \(x^3+3x^2+3x+1=0\)

=>\(x^3+3\cdot x^2\cdot1+3\cdot x\cdot1^2+1^3=0\)

=>\(\left(x+1\right)^3=0\)

=>x+1=0

=>x=-1

c: \(x^3+3x^2-4x-12=0\)

=>\(\left(x^3+3x^2\right)-\left(4x+12\right)=0\)

=>\(x^2\cdot\left(x+3\right)-4\left(x+3\right)=0\)

=>\(\left(x+3\right)\left(x^2-4\right)=0\)

=>\(\left(x+3\right)\left(x-2\right)\left(x+2\right)=0\)

=>\(\left[{}\begin{matrix}x+3=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=2\\x=-2\end{matrix}\right.\)

d: \(\left(x-2\right)^2-4x+8=0\)

=>\(\left(x-2\right)^2-\left(4x-8\right)=0\)

=>\(\left(x-2\right)^2-4\left(x-2\right)=0\)

=>\(\left(x-2\right)\left(x-2-4\right)=0\)

=>(x-2)(x-6)=0

=>\(\left[{}\begin{matrix}x-2=0\\x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=6\end{matrix}\right.\)

 

15 tháng 11 2018

a. 3x(x-2)-x+2=0

3x(x-2)-(x-2)=0

(3x-1)(x-2)=0

=>\(\hept{\begin{cases}3x-1=0\\x-2=0\end{cases}}\)

=> \(\hept{\begin{cases}3x=1\\x=2\end{cases}}\)

=>\(\hept{\begin{cases}x=\frac{1}{3}\\x=2\end{cases}}\)

vậy x thuộc (1/3;2)

15 tháng 11 2018

b. 4x(x-3)-2x+6=0

4x(x-3) -2(x-3)=0

(4x-2)(x-3)

=>*4x-2=0

4x=2

x=1/2

*x-3=0

x=3

vậy x thuộc (1/2;3)

22 tháng 6 2017

a) \(\Rightarrow4x\left(x+3\right)-\left(x+3\right)=0\)

\(\Rightarrow\left(4x-1\right)\left(x+3\right)=0\)

\(\Rightarrow\hept{\begin{cases}4x-1=0\\x+3=0\end{cases}}\) \(\Rightarrow\hept{\begin{cases}4x=1\\x=0-3\end{cases}}\) \(\Rightarrow\hept{\begin{cases}x=\frac{1}{4}\\x=-3\end{cases}}\)

Vậy .....

b) \(\Rightarrow\left(x^2-3x\right)\left(x-2\right)=0\)

\(\Rightarrow\hept{\begin{cases}x^2-3x=0\\x-2=0\end{cases}}\) \(\Rightarrow\hept{\begin{cases}x^2=3x\\x=2\end{cases}}\) \(\Rightarrow\hept{\begin{cases}x=3\\x=2\end{cases}}\)

Vậy \(...........\)

19 tháng 12 2016

a, 5x - 7(3 - x) = 3

=> 5x - 21 + 7x = 3

=> 12x = 24

=> x = 2

b, 4x2 + 3x = 0

=> x(4x + 3) = 0 

=> \(\orbr{\begin{cases}x=0\\4x+3=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=0\\x=\frac{-3}{4}\end{cases}}\)

c, (x + 1)2 - 4x2 =0

=> (x + 1)2 - (2x)2 = 0

=> (x + 1 - 2x)(x + 1 + 2x) = 0

=> (1 - x)(3x+ 1) = 0

=> \(\orbr{\begin{cases}1-x=0\\3x+1=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=1\\x=\frac{-1}{3}\end{cases}}\)

d, x3 - 19x - 30 = 0

=> x3 - 5x2 + 5x2 - 25x + 6x - 30 = 0

=> x2(x - 5) + 5x(x - 5) + 6(x - 5) = 0

=> (x2 + 5x + 6)(x - 5) = 0

=> (x2 + 2x + 3x + 6)(x - 5) = 0

=> (x + 2)(x + 3)(x - 5) = 0

=> x + 2 = 0 hoặc x + 3 = 0 hoặc x - 5 = 0

=> x = -2 hoặc x = -3 hoặc x = 5

=> x thuộc {-2; -3; 5}

19 tháng 12 2016

a, x=2

b, x=0

c, x=1

d, x=2

kb nha

29 tháng 9 2015

a/ => x3 = 64 => x3 = 43 => x = 4

b/ => 4x2 - 12x + 9 - x2 - 10x - 25 = 0 

=> 3x2 - 22x - 16 = 0

=> (x - 8)(3x + 2) = 0

=> x - 8 = 0 => x = 8

hoặc 3x + 2 = 0 => 3x = -2 => x = -2/3

Vậy x = 8 ; x = -2/3

c/ => x3 - x2 - 4x2 + 8x - 4 = 0 

=> x3 - 5x2 + 8x - 4 = 0 

=> (x - 2)2 (x - 1) = 0

=> (x - 2)2 = 0 => x - 2 = 0 => x = 2

hoặc x - 1 = 0 => x = 1 

Vậy x = 2 ; x = 1

 

1 tháng 11 2015

a) \(\Leftrightarrow36+3-11x=0\)

\(\Leftrightarrow-11x=-39\)

\(\Leftrightarrow x=\frac{39}{11}\)

b) \(x^2-2x\frac{1}{4}+\frac{1}{16}-\frac{81}{16}=0\)

\(\left(x-\frac{1}{4}\right)^2=\frac{81}{16}\)

\(x-\frac{1}{4}=\frac{9}{4}\)

\(x=\frac{10}{4}=\frac{5}{2}\)

c) \(x^2\left(x-3\right)-4\left(x-3\right)=0\)

\(\left(x^2-4\right)\left(x-3\right)=0\)

\(\left(x-2\right)\left(x+2\right)\left(x-3\right)=0\)

x = 2 hoặc x = - 2 hoặc x = 3

1 tháng 11 2015

a) \(\frac{8}{2}\)

b) \(\frac{5}{2}\)

c) x=2 hoạc x=-2 hoặc x=3